Static and fatigue behavior of induction-welded single lap carbon fiber reinforced polyetherketoneketone thermoplastic composite joints. (December 2021) - Kwon, Boseong; Choe, Hyeonseok; Jeong, Jaehyeng; Ju, Hyunwoo; Kweon, Jin-Hwe; Nam, Young-Woo
This paper presents details of the mechanical properties related to the static and fatigue strength of carbon fiber reinforced polyetherketoneketone (CF/PEKK) thermoplastic induction-welded composite joints. To better understand the process parameters, the finite element modeling (FEM) of the heat distribution was analyzed based on the generator power, coil coupling distance, coil moving speed, frequency, compaction force, and coil geometry while maintaining the optimal coil speed. The temperature behavior calculated using the simulation model exhibited good agreement with experimental results. A microscopic inspection, non-destructive test (NDT) was conducted to check the morphology characteristics of the welded joints. To check the mechanical performance of the induction-welded specimens, single-lap shear strength (SLSS) tests under static and cyclical fatigue loading conditions were conducted to check the weld qualities from a practical perspective. The mechanical testing results indicated that the static and cyclical fatigue specimens were dominated by a cohesive failure mode with a light fiber tear (LFT). These results suggested that using the optimal process parameters based on multi-physics FEM simulation could potentially improve mechanical performance.